2005
DOI: 10.1080/10413200500313552
|View full text |Cite
|
Sign up to set email alerts
|

Parents' Appraisals, Reflected Appraisals, and Children's Self-Appraisals of Sport Competence: A Yearlong Study

Abstract: This study investigated the contribution of the reflected appraisal process to the ontogeny of children's self-perceptions of physical competence. Emanating from symbolic interactionist thought, reflected appraisals refer to individuals' perceptions of others' evaluations of their abilities. The influence of parents' appraisals of their child's competence on the child's selfappraisals was hypothesized to be mediated by parents' reflected appraisals. Data were collected from a sample of 147 sixth graders and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 45 publications
4
22
0
Order By: Relevance
“…This process thus involves three components, including (1) one's self‐appraisal, (2) the actual appraisal of significant others, and (3) one's perception of the other's appraisal, known as the reflected appraisal (cf. Khanna, 2004), and some empirical evidence supports the claim that reflected appraisals mediate the relation between others’ appraisals and self‐appraisals (Bois, Sarrazin, Brustad, Chanal, & Trouilloud, 2005; Schafer & Keith, 1985; but see Felson, 1989).…”
Section: Reflected Appraisals Of Identitymentioning
confidence: 72%
“…This process thus involves three components, including (1) one's self‐appraisal, (2) the actual appraisal of significant others, and (3) one's perception of the other's appraisal, known as the reflected appraisal (cf. Khanna, 2004), and some empirical evidence supports the claim that reflected appraisals mediate the relation between others’ appraisals and self‐appraisals (Bois, Sarrazin, Brustad, Chanal, & Trouilloud, 2005; Schafer & Keith, 1985; but see Felson, 1989).…”
Section: Reflected Appraisals Of Identitymentioning
confidence: 72%
“…Third, the evidence that perceived appraisal plays a mediating role in the relation between others' evaluation and individuals' self-perception is inconsistent. Whereas some studies have demonstrated the mediating role of reflected appraisal in a variety of domains (e.g., sports ability: Bois, Sarrazin, Brustad, Chanal, & Trouilloud, 2005;interpersonal skills: Ichiyama, 1993;academic and social abilities: Jussim, Soffin, Brown, Ley, & Kohlhepp, 1992;Nurra & Pansu, 2009), other research has failed to support such mediation hypothesis (Felson, 1993;Hergovich, Sirsch, & Felinger, 2002).…”
Section: Children's Appraisals Of Parents' Evaluations: Perception Ormentioning
confidence: 95%
“…The third viewpoint shows that others' actual appraisals could not influence self-perception directly, but could influence self-perception through reflected appraisals (Kinch, 1963;Yue, Huang, 2012;Yue, Huang, & Peng et al, 2008). The study on sport competence of teenagers found that parents' appraisals influence teenagers' self-appraisals through reflected appraisals indirectly, while reflected appraisals had been taken into account because the influence of parents' appraisals on selfappraisals became non-significant (Bois, Sarrazin, Brustad, Chanal, & Trouilloud, 2005). However, the normal college students' reflected appraisals had mediating effects on the relation of others' actual appraisals and self-appraisals on teaching ability (Hu, Yue, & He et al, 2014).…”
Section: Introductionmentioning
confidence: 99%